Penggunaan Tepung Beras dan Gula Merah Pada Pembuatan Petis Daging (Jurnal Ilmu dan Teknologi Hasil Ternak, 2015)
This present work aimed to study the proper concentration of rice flour and palm sugar to produced delighted meat paste based on from phisical, chemical and organoleptic properties. Factorial Randomized Block design was used in the experiment. Meat Broth was supplemented with 2% (A1), 4% (A2), and 6% (A3) of rice flour and supplemented with 10% (B1), 15% (B2), and 20% (B3) of palm sugar to produce meat paste. The meat paste was evaluated for starch content, protein content, viscosity and organoleptic properties. The best result from the experiment was analyzed for Amino Acid Profiles.The Result showed that the addition of rice flour and the palm sugar significantly influenced the quality of meat paste. The combination of these treatments gave a highly significant effect on the viscosity, flavour, colour and taste. The best quality meat paste was obtained from the meat broth supplemented with rice flour 2% (w/v) and 6% (w/v) of palm sugar. The best quality meat paste produced in this study has starch content of 43.03%; viscosity 127.33 centi poise; protein content 13.39%; flavour 6.03; colour 6.25 and taste 5.77.